Site-specific inhibition of EcoRI restriction/modification enzymes by a DNA triple helix. - Hanvey, J C (Nucleic Acids Res, 1990)
The ability of oligopyrimidines to inhibit, through triple helix formation, the specific protein-DNA interactions of the EcoRI restriction and modification enzymes (EcoRI and MEcoRI) with their recognition sequence (GAATTC) was studied. The oligonucleotides (CTT)4 and (CTT)8 formed triplexes in plasmids at (GAA)n repeats containing EcoRI sites. Cleavage and methylation of EcoRI sites within these sequences were specifically inhibited by the oligonucleotides, whereas an EcoRI site adjacent to a (GAA)n sequence was inhibited much less. Also, other EcoRI sites within the plasmid, or in exogenously added lambda DNA, were not inhibited. These results demonstrate the potential of using triplex-forming oligonucleotides to block protein-DNA interactions at specific sites, and thus this technique may be useful in chromosome mapping and in the modulation of gene expression. IMAGES: